Chromosomal features of nucleolar dominance in hybrids between the Neotropical fish Leporinus macrocephalus and Leporinus elongatus (Characiformes, Anostomidae) - Hashimoto, Diogo Teruo [UNESP]; Laudicina, Alejandro; Bortolozzi, Jehud [UNESP]; Foresti, Fausto [UNESP]; Porto-Foresti, Fábio [UNESP] (Springer, 2009)
In the present study, the chromosomal mechanisms of nucleolar dominance were analyzed in the hybrid lineage Piaupara, which resulted from crossing the Leporinus macrocephalus female (Piau double dagger u) and L. elongatus male (Piapara) fish. The analyses demonstrated that, in the hybrid, the nucleolar region inherited from L. elongatus presented higher activity, with expression in 100% of the cells, whereas the nucleolar region from L. macrocephalus appeared active at a frequency of 11.6%. The FISH technique with an 18S probe showed that the ribosomal DNA of the nucleolar region was not lost in the hybrid, and the results therefore demonstrated invariable marks in two chromosomes, each originating from one parent. An interesting difference between the nucleolar regions of the parental species was the association of the NOR with heterochromatic blocks (repetitive DNA) in L. elongatus, which could act as a determinative element in the establishment of this process.
Keywords: Epigenetic phenomenon; Interspecific hybrid; Fish cytogenetic